2022
DOI: 10.3390/plants11101296
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer-Selective Characterization of the Adsorption, Dissipation, and Phytotoxicity of the Plant Monoterpene Pulegone in Soils

Abstract: Plant monoterpenes have received attention for their ecological functions and as potential surrogates for synthetic herbicides, but very little is known about the processes that govern their behavior in the soil environment, and even less about the possible enantioselectivity in the functions and environmental behavior of chiral monoterpenes. We characterized the adsorption and dissipation of the two enantiomers of the chiral monoterpene pulegone in different soils, and their phytotoxicity to different plant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…On the other hand, certain volatile terpenes have demonstrated phytotoxic activity against L. sativa seeds including: 1,8-cineole, sabinene, and α-pinene from Vitex agnus-castus [ 27 ]; p-cymene, γ-terpinene, thymol, carvacrol, and borneol from Thymus eigii [ 28 ]; pulegone [ 29 ], β-pinene, δ 3 -carene, and limonene from Heterothalamus psiadioides [ 30 ]; α-pinene, γ-terpinene, and p-cymene from Eucalyptus grandis [ 31 ]; α-pinene, and β-pinene from Pinus brutia [ 32 ]; eucalyptol, linalool and β-myrcene from Artemisia absinthium [ 33 ]; and 1,8-cineole, β-phellandrene, α-pinene from Majorana hortensis [ 34 ]. Several of these volatile compounds were reported in the GC-MS analysis ( Table 1 ) but in low percentages, except for β-phellandrene which might synergize with the phytotoxic effect.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, certain volatile terpenes have demonstrated phytotoxic activity against L. sativa seeds including: 1,8-cineole, sabinene, and α-pinene from Vitex agnus-castus [ 27 ]; p-cymene, γ-terpinene, thymol, carvacrol, and borneol from Thymus eigii [ 28 ]; pulegone [ 29 ], β-pinene, δ 3 -carene, and limonene from Heterothalamus psiadioides [ 30 ]; α-pinene, γ-terpinene, and p-cymene from Eucalyptus grandis [ 31 ]; α-pinene, and β-pinene from Pinus brutia [ 32 ]; eucalyptol, linalool and β-myrcene from Artemisia absinthium [ 33 ]; and 1,8-cineole, β-phellandrene, α-pinene from Majorana hortensis [ 34 ]. Several of these volatile compounds were reported in the GC-MS analysis ( Table 1 ) but in low percentages, except for β-phellandrene which might synergize with the phytotoxic effect.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the synergistic and/or antagonistic effects of the volatile components in the samples may contribute to their biological activities [ 91 , 92 , 93 , 94 ]. According to Galán-Pérez et al [ 95 ], monoterpenes are potent inhibitors of the germination and growth of several plant species. In addition, the authors note that oxygenated monoterpenes have greater water solubility and inhibitory activity than hydrocarbon monoterpenes.…”
Section: Resultsmentioning
confidence: 99%
“…Disregarding the processes to which allelochemicals are subjected in the soil may result in incorrect predictions of their actual activities [ 21 , 22 , 23 ]. For example, several studies have shown that putative allelochemicals presenting great phytotoxic activity in water or artificial substrates displayed lower or no activity in natural soils [ 18 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%